Democratic Republic of the Congo : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2014)
KEY ISSUES Context and outlook: Despite strong macroeconomic performance under the Fund- supported program (2009-12) with economic activity steadily accelerating and inflation declining sharply, poverty remains pervasive and the economy vulnerable, exposing this progress to reversal. Limited fiscal space and shocks to revenues often offset by expenditure adjustments have not supported pro-poor and critical investment spending necessary for inclusive growth, giving rise to mounting social demands to share in the benefits of the accelerating growth. Focus of consultation: The discussions focused on medium-term policy measures to preserve macroeconomic stability while promoting inclusive growth, improve transparency and good governance in the natural resources sector; and foster financial stability and development. Key policy recommendations: -- Maintain the fiscal anchor of no (net) central bank financing of the budget while creating fiscal space through enhanced domestic revenue mobilization, and improving the quality of public spending through public financial management (PFM) reforms, and building more robust buffers against external shocks. -- Implement measures included in the updated governance matrix agreed with the World Bank and the recommendations of the Extractive Industries Transparency Initiative (EITI) and the National Conference on Mineral Resources Management (NCMRM) to enhance transparency and good governance in the management of natural resources. -- Accelerate reforms of the Central Bank of the Congo (BCC) and the financial sector by (i) passing the central bank law to strengthen its independence and governance, (ii) completing its recapitalization, and (iii) strengthening its analytical capacity, (iv) disengaging from non-core activities, and (v) implement FSAP recommendations to promote financial sector stability and development.